2016
DOI: 10.1590/s0102-05362016003009
|View full text |Cite
|
Sign up to set email alerts
|

Tomato post-harvest durability and physicochemical quality depending on silicon sources and doses

Abstract: This study aimed to investigate the effect of silicon (Si) sources and doses on the physicochemical quality as well as post-harvest conservation of tomato fruits. Treatments were arranged in a 3 x 5 factorial scheme corresponding to sources [calcium silicate, potassium silicate and sodium silicate] and five doses of Si (equivalent to 0, 100, 200, 400 and 800 kg/ha SiO 2 ). Randomized blocks were the experimental design, with four replications. Soluble solids, vitamin C, lycopene, titratable acidity, mature fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 15 publications
5
18
1
2
Order By: Relevance
“…In addition, it gives desirable appearance to the fruits, since it increases their dark reddish pigmentation. Thus, high lycopene contents in the fruits are desirable, both for fresh commercialization and for industrial processing (Carvalho, Fonseca, Silva, Boiteux, & Giordano, 2005;Marodin et al, 2016). The contents obtained in the present study were satisfactory, even at the initial maturity stages.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, it gives desirable appearance to the fruits, since it increases their dark reddish pigmentation. Thus, high lycopene contents in the fruits are desirable, both for fresh commercialization and for industrial processing (Carvalho, Fonseca, Silva, Boiteux, & Giordano, 2005;Marodin et al, 2016). The contents obtained in the present study were satisfactory, even at the initial maturity stages.…”
Section: Introductionsupporting
confidence: 60%
“…The results observed in the present study were higher than those reported by Bernardi et al (2007), evaluating the production and quality of tomato fruits grown in a substrate with zeolite. These authors found values of firmness varying from 7.06 to 14.38 N. Marodin et al (2016) analyzed the postharvest characteristics of tomato as a function of doses of silicate fertilizers and obtained firmness values from 9.5 to 10.6 N. Softening or loss of firmness in the pulp results from the solubilization of pectic substances from the cell wall through the action of pectin methylesterase (PME) and polygalacturonase (PG), whose activities are increased at the beginning of ripening and in the senescence, especially PG, which peaks at the ripe stage (Ferreira et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the application of Si has an effect on plant nutrient uptake and it may enhance phosphorus, calcium and magnesium uptake or decrease nitrogen and potassium uptake . Fertilization with Si revealed positive responses associated with an increase in production and postharvest quality of various vegetables and fruits including lettuce, strawberry and tomato . Moreover, in a recent study it was shown that parameters related to quality attributes of fresh lettuce such as acidity, total soluble solids and vitamin C content increased with salinity, whereas Si application improved these parameters during storage .…”
Section: Introductionmentioning
confidence: 99%
“…30 Fertilization with Si revealed positive responses associated with an increase in production and postharvest quality of various vegetables and fruits including lettuce, 31 strawberry 32 and tomato. 33 Moreover, in a recent study it was shown that parameters related to quality attributes of fresh lettuce such as acidity, total soluble solids and vitamin C content increased with salinity, whereas Si application improved these parameters during storage. 34 The valuable effects of Si have already been proven on crops such as cucumber 35 and tomato 36 grown under salinity stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization supplemented with silicon, has shown positive responses related to the gain in production and post-harvest quality of some vegetables such as lettuce (Resende et al, 2007;Galati et al, 2015b), strawberry (Figueiredo, 2010) tomato (Marodin et al, 2016). In conditions of salt stress, positive effects of this mineral have already been verified in crops such as wheat, cashew, rice, corn, tomato, among others (Tuna et al, 2008;Miranda et al, 2010;Kraska & Breitenbeck, 2010;Lima et al, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 98%